(untitled) - Naisbitt, John (London, 1997)
While the attention of the West has been fixed on the USSR and Eastern Europe, a quieter, cumulative revolution has been taking place in Asia which may have even more profound consequences for world history. As we move towards 2000, Asia will become the dominant region of the world: economically, politically and culturally. Up until the 1990s, the West set the rules. Now, Asians are creating their own rules and will soon determine the game as well. Even Japan will be left behind as the countries of South East Asia, led by the Overseas Chinese and China, increasingly hold economic sway. In the Asian Renaissance, a new network of nations based on economic symbiosis and the enterprise of the Overseas Chinese is emerging in a global shift of the world's centre of economic and political gravity. The Asian continent, from India to Japan, from below the old Soviet Union down to Indonesia, now accounts for more than half of the world's population. And as many as half a billion will be what the West consider middle class. That market is roughly the size of the United States and Europe combined. This is a consumer miracle holding vast economic consequences. Furthermore, a huge urban shift is moving Asia to the information age as it rushes towards computers and telecommunications. There is an unprecedented increase in women entrepreneurs. Asians believe that not only is the cost of the welfare state a heavy burden on competitiveness, but it is also socially destructive; in Asia, families take care of themselves above all else. This raises central questions for the West, especially for the USA and Europe. The modernization of Asia is best understood not as Westernization, but as the Asianization of Asia as the global axis of influence shifts from West to East. The eight Asian megatrends that are changing the world are: from nation states to networks; from export-led to consumer-driven; from Western influence to the Asian way; from government-controlled to market-driven; from villages to supercities; from labour-intensive to high technology; from male dominance to the emergence of women; and from West to East. John Naisbitt is the author of "Megatrends" and "Global Paradox"
Keywords: Châu Á,Asia; Điều kiện xã hội,Social conditions; Thế kỷ 20,20th century